Identification and design of performance indicators in the shoe industry as tools to evaluate profitability - Villafana, Inés (2021)
The shoe industry is underdeveloped in Peru. Within Lima, companies of various levels of profitability manage their businesses in their own way (some empirically). Sponsored by the Scientific Research Institute (IDIC), this qualitative (exploratory) research has been developed by conducting interviews with experts (2013), concluding that 83,33 % of these companies do not have key performance indicators, thus proposing them for both commercial and production areas.